A cross-sectional study of pedagogical strategies in nursing education: opportunities and constraints toward using effective pedagogy - Pagnucci, Nicola (BMC Med Educ, 2015)
BACKGROUND: The continuous, rapid evolution of medical technology, the public need for ever more complex health-care services and the stagnant global economic situation have posed difficult new challenges for the nursing profession. The need to integrate knowledge, technical skill and ethical conduct in nursing practice has become ever more evident, particularly in response to the emerging challenges over recent years. Major research studies have highlighted that high-quality responses to health needs is highly dependent on both the education received by health care professionals and the pedagogical strategies employed in such training. The aim of this study was to identify the pedagogical strategies used by teachers in nursing programs in the Italian university system and to classify them according to the didactic architectures that are used. METHODS: The study sample was recruited from the entire population of nursing instructors teaching in all years of their respective programs, in every Italian university with a nursing program. A three-part questionnaire, based on a Calvani taxonomy, was designed to collect both demographic and cultural information on the sample subjects, as well as the pedagogical strategies that they may have used in their teaching practices, was administered to all nursing instructors. A five-point Likert scale was used to measure the frequency of use of different pedagogical strategies. RESULTS: On the whole, 992 teachers participated in the study (80.1 % of the teachers contacted). Experience data suggest a highly-educated overall instructor population. The settings in which the participants carried out their teaching activities were represented mostly by large lecture halls and the number of students in their classes were for the most part rather large; over 60. Frequency of use revealed that the most commonly used method was the traditional lecture. Indeed, 85.7 % of the respondents “often” or “always” used pedagogical strategies belonging to a ‘receptive architecture’. CONCLUSIONS: Any redefining of approaches to nursing education must consider several key factors to ensure the promotion of student-focused pedagogical strategies. Only through the implementation of such pedagogical practices will it be possible to generate the knowledge and skills necessary for future professionals to be able to adequately respond to the ever more complex health care needs of the population.